The Current Global Political Scenario: In the light of Jewish history - Muhammad Asif; Aisha Sadaf (jihat-ul-islam, 2021)
This article aims to study the characteristics and introduction of Jews and their religion Judaism and its impact on the global world in the light of Jewish history. nAccording to Jewish teachings, Jews are God’s loving, favorite and chosen people. On the Day of Judgment they are free from the concept of punishment and surely deserve Paradise, because in the Hereafter Abraham will be seated at the gates of hell and will not allow any Israelis to enter into it. Literature of the Jewish religion creates a sense of superiority in this nation because of the concept of being a Chosen People. The concept of superiority, the killing of Gentiles, terrorism, suiciding attacks are the part of Jewish culture. It is a Jewish religious obligation that has been greatly affected to the non-Jewish nations, especially the Muslim Ummah. Jewish control of the global economy is a very dangerous situation for Muslims.